Peran Komunikasi Interpersonal Guru Dalam Pembentukan Karakter Anak Usia Sekolah - Magdalena Kartikasari Tandy Rerung; Henilia Yulita (Journal on Education, 2024)
The formation of a child's character is not just innate, but rather a continuous process that then becomes the child's character. An interpersonal communication approach can help teachers have better resilience in educating their students' characters. This study uses a qualitative method with the research location at the UPT SD Kristen Nafiri Sion school, Jl. Lipungan Tanete, Lembang Lipungan Tanete, Kec. Kurra, Kab. Tana Toraja, South Sulawesi Province. The technique used was an interview with four sources consisting of the principal, homeroom teacher, subject teacher, and honorary teacher from the UPT SD Kristen Nafiri Sion school. This study found the benefits of implementing interpersonal communication through openness, empathy, support, positive acceptance, and similarities between educators, teachers, and the principal.